(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Caste discrimination has been a persistent social issue in India for centuries. This theoretical overview provides a comprehensive understanding of caste discrimination, its causes, and its consequences. The overview explores the historical, social, and cultural factors that have contributed to the persistence of caste discrimination and examines the various forms of discrimination faced by individuals of lower castes in different domains of society. It also discusses the consequences of caste discrimination, including its impact on individual well-being, social cohesion, and economic development. Finally, the overview considers the strategies and interventions that have been used to address caste discrimination and the challenges associated with implementing these interventions effectively. This theoretical overview contributes to the existing literature on caste discrimination, providing a comprehensive understanding of the issue and highlighting the need for continued research and action to address this pressing social problem.